CONTAMINAÇÃO POR ÁGUA SUBTERRÂNEA EM SÃO JOSÉ DO RIO PRETO (SP) * CONTAMINAÇÃO POR NITRATOS - Castro, Sérgio C. S.; Arid, F. M.; Santos, C. C. M. dos; Silva, R. A.; Cunha, I. P. da (Águas Subterrâneas, 1992)
INDISPONÍVEL